Strategi Adaptasi Umat Hindu Memasuki Era Baru: Refleksi Sosiologi Hindu Menyikapi Revolusi Industri 4.0, Pandemi Covid-19, dan Society 5.0 - Ida Bagus Gde Yudha Triguna; Anak Agung Inten Mayuni; Nanang Sutrisno (Jayapangus Press, 2020)
The Industrial Revolution 4.0, the Covid-19 Pandemic, and the Society 5.0 are global phenomena that are driving social change towards a new era of the world society. Hindus also have to carry out adaptation strategies, both at the structural and cultural level in order to enter this new era. Sociological reflections on Hindu adaptation strategies are expressed through the phenomenological method which emphasizes the individual agency dimension and its integration with structural dynamics. The ability of Hindus to exercise control dialectics on the acceleration of information technology, ideological regulation and socio-cultural structures change in the new era is a determinant of success in their adaptation strategy.